12 Men Who Shook the World - Knoche, Phillip and Keith; Nang ChanYeema (Boise, ID USA Pacific Press Publishing Association, 1984)
Discover the unique characteristics and the secret of the 12 disciples remarkable impact on civilization.
Keywords: Adult Nonfiction